Makna Teologis Bahtera Nuh Ditinjau Dari Ibrani 11:7 Serta Relevansinya Terhadap Pertumbuhan Iman Pada Jemaat GESBA Shaloom Kaima - Kambong, Hizkia Joel; Ranting, Hermin; Rakim, Ristan; Nendissa, Julio Eleazer (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
This study aims to examine the theological meaning of Noah's Ark based on Hebrews 11:7 and analyze its relevance to the faith growth of the GESBA Shaloom Kaima congregation. Noah is portrayed as a righteous and blameless figure entrusted by God to carry out the mission of saving humanity through the construction of Noah's Ark. Due to his faith, Noah and his family were saved from the Flood. This research employs a qualitative method with a descriptive approach, supported by data collection techniques such as interviews and literature studies. The interviews were conducted in an unstructured manner, allowing the researcher to interview 9 individuals, consisting of 1 pastor, 2 church council members, and 6 congregants, without strict guidelines. Literature studies were used to interpret and gather data from books and journals relevant to this research. The results show that the theological meaning of Noah's Ark significantly influences the faith growth of the GESBA Shaloom Kaima congregation and effectively nurtures the congregation's spiritual life. The study identified several key points related to the theological meaning of Noah's Ark, including a general understanding of the story of Noah's Ark in the Bible, an interpretation of the theological meaning of Noah's Ark from the perspective of Hebrews 11:7, and its relevance when integrated into Christian education and sermon materials. These findings also indicate a connection between the theological meaning of Noah's Ark and the faith growth of the GESBA congregation, including the application of the principles of Noah's Ark in daily life. Therefore, the meaning of Noah's Ark can serve as a guide for the GESBA Shaloom Kaima congregation in building a foundation for their faith growth.